Audio Description for Cinema and TV Production in Lithuania - Laura NIEDZVIEGIENĖ (transLogos: Translation Studies Journal, 2023)
Recently, there has been an increase in the engagement of initiatives and projects pertaining to individuals with disabilities in Lithuania. Local and foreign cultural, educational, or other institutions are often interested in partnerships on such topics. However, a prevailing challenge lies in locating individuals in Lithuania who possess prior experience in the realm of accessibility. Insufficient dissemination of information regarding such activities contributes to this difficulty. Lithuanian practice shows that local or foreign institutions wishing to establish partnerships in the field of accessibility (or specifically in the field of audio description) find the right people only after a long search. This article acquaints the reader with the concept of audio description and explores the Lithuanian terminology associated with this phenomenon in detail. The paper provides a clear and concise outline of information on the visually impaired population and on the increasing popularity of accessible film and television production in our country. Hopefully, this article will improve the dissemination of information about audio description services in Lithuania, enabling researchers and practitioners to identify institutions and individuals involved in the field of audio description in our country, as well as understand the legal framework governing audio description services.